Strengthening Farmer Adaptive Capacity Through Farms of the Future Approach in Nyando, Western Kenya - Kimeli, Philip; Nyasimi, Mary; Radeny, Maren A.O. (Springer, 2017)
Rapidly changing climatic conditions in East Africa are increasing sources of vulnerability for rural agricultural communities. Current agricultural practices and institutional coping mechanisms are unable to cope with these changes, and calls for adaptation in agricultural systems. The CGIAR Research program on Climate Change, Agriculture and Food Security (CCAFS) has developed the Climate Analogue tool that connects sites with statistically similar (‘analogous’) climatic conditions, across space and time. The tool can and has been used to connect farmers and agricultural stakeholders to their plausible future climates through the Farms of the Future (FotF) approach—where farmers learn about potential adaptation strategies and institutional innovations through farmer–to–farmer exchanges between analogue sites. The FotF approach can be used together with ongoing support for participatory action research to build reflective capacity and awareness of challenges farmers likely to face and to identify and develop possible solutions among farmers and other agricultural stakeholders. This paper documents the learning experiences of farmers from Nyando, in Western Kenya during through participation in the climate learning journey across other counties in Kenya. The paper also shows how these farmers are planning to use their learning experiences to design local adaptation plans of actions.